The Digestible Methionine and Cystine Requirements for Commercial Layers - Cao , T.; Weil, J.T.; Maharjan, P.; Lu, J.; Coon, C.N. (International Journal of Poultry Science, 2020)
Background and Objective: Two experiments were conducted to determine the total sulfur amino acid requirements in laying hens. The objective of Experiment 1 was to determine the digestible methionine and cystine requirements for laying hens. An additional experiment (Experiment 2) was conducted to determine the cystine requirement for laying hens and determine the utilization efficiencies of supplemental methionine and cystine to meet the cystine requirement. Materials and Methods: In Experiment 1, one hundred and seventy-six laying hens were randomly assigned into 11 dietary treatments for a six-week period. One group of hens received a corn-soybean meal control diet containing 2,899 kcal ME kg–1 and 19.5% CP, while the remaining ten groups of hens received 10 test diets containing 2,850 kcal ME kg–1 and 15% CP. Five diets were deficient in cystine (0.148% digestible cystine), containing digestible methionine levels of 0.143, 0.240, 0.337, 0.434 and 0.531% and another five diets were excessive in cystine (0.450% digestible cystine), containing digestible methionine levels of 0.143, 0.231, 0.317, 0.407 and 0.495%. An additional experiment (Experiment 2) was conducted by assigning one hundred sixty laying hens to one of two series of diets, which were formulated to contain 0.319% digestible methionine and 0.148% digestible cystine, same as that in Experiment 1, with exception of the methionine level. Four levels of equimolar amounts of methionine or cysteine (½ cystine) were added to the basal diet. The added levels were 0.05, 0.10, 0.15 and 0.20% for methionine and 0.04, 0.08, 0.12 and 0.16% for cystine since the molecular weight of cysteine (½ cystine) is 80% of that of methionine. Data generated from each experiment was analyzed using the general linear models (GLM) and analysis of variance procedures with the help of statistical analysis software (SAS). A second-order polynomial regression analysis was conducted in order to determine the methionine requirements for laying hens. Results: The results showed that the requirement of digestible methionine and digestible cysteine for laying hens were 354 and 184 mg hen–1 day–1 for egg mass (EM), 349 and 193 mg hen–1 day–1 for feed conversion, 437 and 325 mg hen–1 day–1 for body weight change (BWC) and 367 and 189 mg hen–1 day–1 for EM+BWC, respectively. Deficient or excessive dietary methionine produced an increase of methionine degradation due to the increased body weight loss or the excessive dietary methionine, correspondingly. Optimum dietary methionine levels resulted in increased liver SAM/SAH concentration ratios (s-adenosylmethionine/s-adenosylhomocysteine) and decreased homocysteine (Hcy) levels. Conclusion: The results demonstrated that the utilization efficiencies of methionine and cysteine (½ cystine) were 100% on an equimolar basis for egg mass and 90% on an equimolar basis to prevent loss of body weight. When methionine was used to meet the cystine requirement, an utilization efficiency of 80% was adequate on a weight and concentration basis for egg mass and 72% for body weight maintenance. The practice of feeding ingredients with a substantial digestible cystine level for supporting body weight may be beneficial for laying hens.